2014
DOI: 10.1016/j.cortex.2014.01.018
|View full text |Cite
|
Sign up to set email alerts
|

A perfusion fMRI investigation of thematic and categorical context effects in the spoken production of object names

Abstract: The context in which objects are presented influences the speed at which they are named. We employed the blocked cyclic naming paradigm and perfusion fMRI to investigate the mechanisms responsible for interference effects reported for thematically-and categorically-related compared to unrelated contexts. Naming objects in categorically homogeneous contexts induced a significant interference effect that accumulated from the second cycle onwards. This interference effect was associated with significant perfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
39
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 70 publications
3
39
1
Order By: Relevance
“…Thematic groupings did not elicit this behavioral effect (de Zubicaray et al, 2014), though they have been found to elicit the closely related cumulative semantic interference effect (Rose & Abdel Rahman, 2016). …”
Section: Systematic Review Of Dissociation Between Taxonomic and Themmentioning
confidence: 89%
“…Thematic groupings did not elicit this behavioral effect (de Zubicaray et al, 2014), though they have been found to elicit the closely related cumulative semantic interference effect (Rose & Abdel Rahman, 2016). …”
Section: Systematic Review Of Dissociation Between Taxonomic and Themmentioning
confidence: 89%
“…The contribution of de Zubicaray et al (2013) uses data from neuroimaging to help specify the mechanism underlying the cumulative semantic interference effect in which the speed of picture naming shows a monotonic increase as a function of the number of previously named semantically related pictures and is not mitigated by changing the number of stimuli between the related items (Howard, Nickels, Coltheart, & Cole-Virtue, 2006). The originally proposed explanations of this effect include several familiar concepts within the domain of language production such as shared activation of semantic features, priming of semantic-to-lexical representations, and lexical selection by competition (Howard et al, 2006), although the last component has been recently questioned by Oppenheim, Dell, and Schwartz (2010) who simulated the effect using a computational model based on an account of lexical selection based on reaching a threshold rather than competition.…”
mentioning
confidence: 99%
“…Oppenheim et al's (2010) account included other differences from Howard et al's (2006) account that led de Zubicaray to use perfusion functional magnetic resonance imaging (fMRI) to examine the perfusion signal changes associated with the cumulative semantic interference effect. In using perfusion fMRI to help understand the neurocognitive mechanism underlying this effect, de Zubicaray et al (2013) are able to identify regions associated with the hallmark of the effect (i.e., the monotonically increasing difficulty with naming additional within-category exemplars) and are also able to powerfully constrain accounts of cumulative semantic interference.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies reporting LIFG involvement tended to average data over all cycles or include cycle as a covariate of no interest (de Zubicaray, Johnson, Howard, & McMahon, 2014). This is potentially problematic as the interference effect manifests from the second cycle onwards, and the opposite pattern of semantic priming is sometimes observed in the first cycle, suggesting two different processes/mechanisms (i.e., priming and interference) might thus be confounded (see Belke & Stielow, 2013;Damian & Als, 2005).…”
Section: Neuroanatomical Regions Implicated In Semantic Interferencementioning
confidence: 99%